A statutory review of adjudicators’ determinations under the Construction Contracts Act 2004 (WA) by the State Administrative Tribunal and the Courts of Western Australia - Steensma, Auke (Curtin University, 2018)
The Construction Contracts Act 2004 (WA) commenced on 01 January 2005. From 2005 until 30 June 2017, the Construction Contracts Act 2004 (WA) was used by those seeking a resolution to payment claim disputes within the Western Australian construction industry on 1822 occasions. The statutory legislation provides three mechanisms that give rise to access in the Courts of Western Australia and the State Administrative Tribunal. This research will examine the three mechanisms.